Role of Alveolar Macrophages in Chronic Obstructive Pulmonary Disease - Vlahos, Ross; Bozinovski, Steven (Frontiers in Immunology, 2014)
Alveolar macrophages (AMs) represent a unique leukocyte population that responds to airborne irritants and microbes. This distinct microenvironment coordinates the maturation of long-lived AMs, which originate from fetal blood monocytes and self-renew through mechanisms dependent on GM-CSF and CSF-1 signaling. Peripheral blood monocytes can also replenish lung macrophages; however this appears to occur in a stimuli specific manner. In addition to mounting an appropriate immune response during infection and injury, AMs actively coordinate the resolution of inflammation through efferocytosis of apoptotic cells. Any perturbation of this process can lead to deleterious responses. In chronic obstructive pulmonary disease (COPD), there is an accumulation of airway macrophages that do not conform to the classic M1/M2 paradigm. There is a skewed transciptome profile that favors expression of wound healing M2 markers, which is reflective of a deficiency to resolve inflammation. Endogenous mediators that promote distinct macrophage phenotypes are discussed, as are the plausible mechanisms underlying why AMs fail to effectively resolve inflammation and restore normal lung homeostasis in COPD.